‘No Austrian Mother Does This to Sleep Without a Baby!’ Postnatal Acculturative Stress and ‘Doing the Month’ Among East Asian Women in Austria: Revisiting Acculturation Theories From a Qualitative Perspective - Seidler, Yuki; Seiler-Ramadas, Radhika; Kundi, Michael (Frontiers in Psychology, 2020)
Acculturative stress is a phenomenon describing negative emotions experienced by immigrants in their socio-cultural and psychological adaptation process to the host society’s dominant culture and its population. Acculturative stress is assumed to be one the reasons for higher prevalence of postnatal depression among immigrant women compared to non-immigrant women. Theories and models of acculturation and coping strategies suggest that certain cultural orientations or behaviors could mitigate acculturative stress and postnatal depression. Nevertheless, quantitative studies applying these theories have so far revealed inconsistent results. Given this background, we ask: what can a qualitative study of immigrant women’s postnatal experiences tell us about the interrelationships between immigrant mothers’ acculturation behaviors or cultural orientations, and maternal psychological health? Particularly, we explore the postnatal experiences of Chinese and Japanese women who gave birth in Austria, focusing on their experiences and behaviors influenced by their heritage culture’s postnatal practices (zuò yuè zi and satogaeri). Theoretically, we apply Berry’s acculturation model through a focus on what we call ‘Postnatal Acculturative Stress’ (PAS). By doing so, we identify factors that prevent or mitigate PAS. Another aim of this article is to critically reassess Berry’s model in the context of postnatal care and maternal psychological health. Data were analyzed using a combination of deductive and inductive method through the application of directed content analysis and phenomenological approach. Women’s postnatal experiences were summarized as an ‘unexpected solitary struggle in the midst of dual identity change’ in four specific domains: postnatal rest and diet, social support, feelings towards significant others and identity. Preventive and mitigating factors against PAS included trust (in self and one’s health beliefs) and mutual respectful relationships with and between the significant others. The application of Berry’s acculturation model provided a useful framework of analysis. Nevertheless, the multifarious complexity involved in the process of acculturation as well as different power dynamics in the family and healthcare settings makes it difficult to draw causal relationships between certain acculturation behaviors or cultural orientations with specific health outcomes. Health professionals should be aware of the complex psychosocial processes, contexts as well as social environment that shape immigrants’ acculturative behaviors.